KINERJA DINAS PENGENDALIAN PENDUDUK KELUARGA BERENCANA PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK (DP2KBP3A) KABUPATEN BANGLI DALAM MEMINIMALISIR PERNIKAHAN DINI - Paramitha, Ida Ayu Candra; Winaya, I Ketut; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2021)
Early marriages that occur in adolescents in Bangli Regency continue to increase every year. The Office of Family Planning for Women Empowerment and Child Protection of Bangli Regency continues to strive to improve its performance in providing prevention and handling of cases related to women and children, such as early marriage. The research method used is descriptive qualitative with data collection techniques through observation, interviews and documentation studies. Based on the theory of performance according to Dwiyanto, the results of the study show that the performance of the Bangli District Women's Empowerment and Child Protection Planning Office in minimizing early marriage has gone well, but has not been optimal. There are still obstacles that cause service delivery to be not optimal, such as the limited number of employees, limited funds in program implementation, lack of public interest in participating in the socialization. Keywords: Performance, Women Empowerment and Child Protection, Early Marriage